Research trend of circulating tumor DNA associated with breast cancer from 2012 to 2021: A bibliometric analysis - Zeqi Ji; Lingzhi Chen; Qiuping Yang; Huiting Tian; Jinyao Wu; Daitian Zheng; Jiehui Cai; Yexi Chen; Zhiyang Li (Frontiers in Oncology, 2023)
BackgroundRecently, ctDNA has become the focus for scientists with respect to personalized treatment, early screening, precise diagnosis, and prognosis of BC. This paper aims to use bibliometric analysis to investigate the research status and future trends in this field.MethodsAll the related literature in the field of ctDNA and breast cancer was gathered from the Web of Science Core Collection. Data analyses were performed with R package Bibliometrics, VOS viewer 1.6.18, and online analysis in WoS. IBM SPSS (version 26.0) was used for statistical analysis.ResultsA total of 739 publications, including 472 articles and 267 reviews, were retrieved. The overall number of articles published showed an upward trend. The United States has the largest number of published articles (266 papers) and citations (20,225 times). The most productive journal was Clinical Cancer Research. Cristofanilli M was the most prolific author, while Carlos C was the most cited one. The most frequent keywords excluding the search subject were “liquid biopsy”, “plasma”, “mutations”, “metastatic breast cancer”, “acquired resistance”.ConclusionThis article explored the application value of ctDNA in breast cancer with bibliometric analysis, offering an overall and intuitive understanding of this topic and revealing the study trends in the past ten years.